Pengembangan Multimedia Pembelajaran Bahasa Arab Berbantuan Komputer di SMA/SMK Muhammadiyah - Tantiana Isnaningsih (AN NUR: Jurnal Studi Islam, 2015)
This article describe stages in developing computer multimedia for Arabic learning in SMA/SMK Muhammadiyah by analyzing the students’ achievement before and after using the program in their learning. The research results showed that the steps in developing computer multimedia included six stages, namely information collection, learning development planning, product development, initial product, evaluation, and final product. The results of this research and development study showed that the multimedia quality (1) from the product performance aspect was in the good category with a mean of 3.75, (2) from the subject matter quality aspect was in the good category with a mean of 3.89, and (3) from the attractiveness aspect was in the attractive category because the students stated that learning Arabic was interesting and fun. The results of the pretest and posttest in the field try-out showed that there was a significant improvement in the students’ achievement before and after using the product of computer-assisted learning multimedia with t = 12.84 and t 0.05 = 2.02. The results showed that the product of the development of computer-assisted learning multimedia was appropriate as learning multimedia in Arabic learning.